(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
In this article, the results of a study involving the implementation of an experimental program of specialized physical training with a focus on the development of psychophysical qualities of future police officers in higher education institutions of the Ministry of Internal Affairs (MIA) are highlighted. The aim was to assess the effectiveness of the experimental program of specialized physical training with a focus on the development of psychophysical qualities of future police officers. The methods included theoretical analysis and generalization of scientific-methodical literature, pedagogical testing, and pedagogical experimentation. The results obtained from the research were processed using methods of mathematical statistics, providing a qualitative and statistically sound analysis of indicators with the help of computer tools such as "Excel" and "Statistica 10". Fifty-two first-year cadets from the Prekarpathian Faculty of the National Academy of Internal Affairs in Ivano-Frankivsk participated in the study, forming control and experimental groups with 26 cadets each. The formative experiment lasted for nine months. Results. It was established that the use of the experimental program significantly improved the level of physical health, aerobic endurance, and physical fitness. Moreover, there was a significant reduction in the level of aggression among cadets, and their stress resistance improved significantly. The evaluation of the developed program revealed its higher efficiency compared to the existing physical training program in higher education institutions of the Ministry of Internal Affairs of Ukraine. Conclusions: The number of cadets who increased their level of physical health was higher in the experimental group compared to the control group, where a deterioration in physical health indicators was observed. In the experimental group, no cadets were found with below-average or average levels of physical health, while in the control group, these functional levels were observed in 15.39% of the surveyed cadets. Aerobic endurance was determined using the "beep test" after completing the physical education. Analyzing the results, we found a difference in the average results of VO2max(v) by 3.21 ml/kg/min between the control group (39.54±6.84 ml/kg/min) and the experimental group (42.75±5.74 ml/kg/min) after the pedagogical experiment. A significant improvement in the overall level of physical preparation was also observed in the experimental group after the experiment. In the control group, 15.38% of the surveyed cadets had below-average and average levels of physical preparation, while in the experimental group, no cadets were found with this level of physical preparation.